Bel canto : a novel - Patchett, Ann. (New York : Perennial, 2002)
It is a perfect evening -- until a band of gun-wielding terrorists breaks in through the air-conditioning vents and takes the entire party hostage. But what begins as a panicked, life-threatening scenario slowly evolves into something quite different, as terrorists and hostages forge unexpected bonds and people from different countries and continents become compatriots.
Keywords: Women singers -- Fiction; Victims of terrorism -- Fiction; Embassy buildings -- Fiction; Hostages -- Fiction; South America -- Fiction; Psychological fiction; Love stories